The Evolution of Street Structures: A Morphological Study (Journal of Engineering, 2024)
Morphological structures of urban streets in Baghdad have been deciphered by using practical methodologies inclusive of data collection, digitization, and identification processes. This paper uses street pattern morphological analysis in a typical Middle Eastern city, in this case, Baghdad, from organic configurations to modern metropolitan sprawl. It is based on historical maps and satellite images, supported by field surveys. Six distinct street patterns have been identified that have influenced the formation of Baghdad’s urban development and continuity, focusing attention on the ancient city configuration and current planning principles. Of great interest is the fact that there are calls for the retention of the urbanism historical fabric in the cities with new growth at the same time there are calls for methodologies that are responsive to the sociocultural energy characteristic of the cities in the Middle East. This study adds to the general body of literature on urban morphology and further provides detailed insight into the morphology of streets in Baghdad and other similar towns. The research, therefore, shows evidence of the need for recognizing street morphology roles in the form and function of urban landscapes and will advocate for environments reflective of historical context in line with the needs that modern urban life requires. Results will demonstrate how streets change based on influences from culture and socio-economic factors. They conclude that streets developed in the light of cumulative processes, directions, and scales of development. This research is taken up to comprehend urban morphology leading towards sustainable and culturally responsive designs.